Interpersonal adaptation on problematic mobile internet use among college students: the mediating role of fear of missing out and self-differentiation. - Zhengyu, Wu; Haiyan, Zhao; Shuhui, Huo; Wei, Li; Xueqi, Zhang; Jianqin, Cao (Psychology, Health & Medicine, 2026)
Previous studies have established associations between interpersonal adaptation and Fear of missing out (FoMO), self-differentiation, and problematic mobile Internet use (PMIU). However, the mediating roles of FoMO and self-differentiation in linking interpersonal adaptation to PMIU among Chinese university students remain unclear. In this study, a sample of 540 university students completed self-report measures using the Interpersonal Adaptation Scale, the Fear of Missing Out Scale, the Self-differentiation Scale, and the Problematic Mobile Internet Use Scale. The results supported a sequential mediation model. Specifically, poorer interpersonal adaptation was associated with higher levels of FoMO, which in turn was linked to lower self-differentiation, ultimately leading to more severe problematic mobile Internet use. In other words, difficulties in interpersonal adaptation may predict a heightened sense of FoMO, which could impede self-differentiation and consequently contribute to the development of PMIU.